Diverting colostomy induces mucosal and muscular atrophy in rat distal colon. Issue 9 (September 1994) - Kissmeyer-Nielsen, P; Christensen, H; Laurberg, S
Abstract : The progress of adaptive changes in the left colon after diverting colostomy was studied in rats using stereological techniques. Standardised segments of left colon proximal and distal to the colostomy was examined after 0, 1, 2, 4, or 12 weeks. In excluded colon the mucosal weight was reduced by 37% (p < 0.01) and the luminal surface area by 47% (p < 0.01) after four weeks and reached a steady state at this point of time, as no further reduction was seen from 4 to 12 weeks. The number of proliferating crypt cells was determined immunohistochemically after in vivo labelling with bromodeoxyuridine and was compared with the total number of colonocytes. Total bowel rest leads to a reduction in the number of proliferating epithelial cells and not to a reduced average life span. The weight of the muscularis propria decreased by 32% after four weeks (p < 0.01) and by 48% after 12 weeks (p < 0.001), whereas the weight of the submucosa was unchanged. No adaptive changes were found in segments proximal to the colostomy. These results show that the wall composition of defunctioned colon in rats is radically changed resulting from a mucosal and muscular atrophy, and from a reduction in luminal surface area.